Challenges and Opportunities on Urban Water Quality in Mexico City - Mazari-Hiriart, Marisa; Tapia-Palacios, Marco A.; Zarco-Arista, Alba E.; Espinosa-García, Ana C. (Frontiers in Environmental Science, 2019)
Mexico City has a population of 9 million inhabitants and was settled on a lakebed with high seismic potential. It is currently embedded in the Mexico City Metropolitan Area, which encompasses 22 million inhabitants and which was self-sufficient in water in the past, but currently extracts 70% from the regional aquifers and imports about 30% of the water required. Groundwater represents its main water source but its water quality is increasingly threatened. The purpose of this study was to determine the water quality in areas related to seismic fractures, which may increase the vulnerability of water provision, and to identify specific zones that could be affected. Official water quality data from the period 2002 to 2017 was analyzed and compared to recent data taken in wells in the city after the September 2017 earthquake. Statistical and temporal analyses were performed in order to understand the evolution and spatial distribution of water quality. The results show that free chlorine was below the limits according to the Mexican regulatory framework, while the presence of fecal coliforms, aluminum, ammonia, iron, and manganese exceeded the standards. The presence of arsenic, boron, and chrome was detected in some areas. Clusters show specific parameters that increase with time: turbidity, sulfates, nitrates, arsenic, manganese, lead, and iron. These tendencies could imply the deterioration of groundwater quality and a potential effect on the health of the exposed population. Spatially, vulnerability was observed in Iztapalapa, Tláhuac, Xochimilco, and Coyoacán. Wells coincide spatially with some of the geological damaged areas from the earthquakes in Iztapalapa and Xochimilco. In addition to water quantity, water quality represents a challenge for the urban future, since water disinfection systems are limited to treating the diversity of compounds detected. The water quality-monitoring program must be changed to improve its capacities within a framework of sustainable water management in different regions of the city, and based on the season, considering the potential exposure to the city’s population. This represents an opportunity to propose a strategic plan for the groundwater system in order to improve conditions toward a more equitable and sustainable pathway for Mexico City.